Smart Phone Addiction among Undergraduates in Oyo State, Nigeria: Need for Counselling Therapeutic Approaches - TIAMIYU, Kamoru Abidoye; IBRAHEEM, Islamiyyah Olajire; AJIBOLA, Busayo Omolade (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2025)
Smartphone addiction has become an increasingly pressing issue among university students globally, with undergraduates in Oyo State, Nigeria, exhibiting similar patterns of excessive smartphone use. The proliferation of mobile technologies and social media platforms has contributed to maladaptive behaviours that negatively impact students’ academic performance, mental health, and social relationships. This paper investigates the growing concern of smartphone addiction among undergraduate populations in Oyo State and emphasises the urgent need for effective psychological interventions. The primary aim of this paper is to explore and recommend counselling therapeutic approaches that can help mitigate smartphone addiction and promote healthier technology usage among students. Employing a narrative literature review method, this research synthesises findings from empirical studies, theoretical frameworks, and global counselling practices to comprehensively understand the issue. Findings from the literature reveal that multiple factors, including psychological stress, low self-esteem, peer influence, and the constant availability of mobile applications, influence smartphone addiction. The review identifies counselling strategies such as Cognitive-Behavioural Therapy (CBT), Motivational Enhancement Therapy (MET), Solution-Focused Brief Therapy (SFBT), Mindfulness-Based Interventions, and Rational Emotive Behaviour Therapy (REBT) as practical therapeutic approaches. The paper concluded that the importance of integrating evidence-based counselling methods into institutional support systems lies in addressing smartphone addiction. The paper contributes to the growing discourse on digital wellness. It offers a framework for educators, counsellors, and policymakers seeking to promote mental health and academic success among undergraduates in Nigeria.